Geochemical and sedimentological responses of arctic glacial Lake Ilirney, chukotka (far east Russia) to palaeoenvironmental change since ∼51.8 ka BP. (1st November 2020) - Vyse, Stuart A.; Herzschuh, Ulrike; Andreev, Andrei A.; Pestryakova, Lyudmila A.; Diekmann, Bernhard; Armitage, Simon J.; Biskaborn, Boris K.
Abstract: Palaeoenvironmental reconstructions with temporal coverages extending beyond Marine Isotope Stage (MIS) three are scarce within the data sparse region of Chukotka, Far East Russia. The objective of this paper is to infer palaeoenvironmental variability from a 10.76 m long, OSL- and 14 C- dated sediment core from Lake Ilirney, Chukotka (67°21′N, 168°19′E). We analysed high-resolution sediment-geochemistry (XRF), sedimentology (TC, TN, TOC, grain-size), mineralogy (XRD) and preliminary micropalaeontological data (diatoms and pollen) from the core as well as acoustic sub-bottom profiling data from the lake basin. Our results affirm the application of XRF-based sediment-geochemical proxies as effective tracers of palaeoenvironmental variability within arctic lake systems. Our study reveals that a lake formed during MIS3 from 51.8 (±4.1) ka BP, following extensive MIS4 glaciation. Catchment palaeoenvironmental conditions during this time remained harsh associated with the continued presence of a catchment glacier until 36.2 (±2.6) ka BP. Partial amelioration reflected by increased diatom, catchment vegetation and lake organic productivity and clastic sediment input from mixed sources from 36.2 (±2.6) ka BP resulted in a lake high-stand ∼15 m above present and is interpreted as evidence of a more productive palaeoenvironment coincident with the MIS3 interstadial optimum. A transitional period of deteriorating palaeoenvironmental conditions occurred ∼30–27.9 ka BP and was superseded by periglacial-glacial conditions from 27.9 (±0.8) ka BP, during the last glacial maximum. Deglaciation as marked by sediment-geochemical proxies commenced at 20.2 (±0.8) ka BP. Our findings are compared with lacustrine, Yedoma and river-bluff records from across Beringia and potentially yield limited support for a marked Younger Dryas cooling in the study area. Highlights: XRF proxies effectively represent sedimentological variables in Arctic glacial lakes. The MIS4 glaciation was more extensive in Chukotka than during MIS2. Lake formation commenced during the early MIS3 at ̴ 51.8 ka BP. A MIS3 interstadial optimum and lake high-stand is inferred. Evidence for a pronounced younger dryas cooling is limited.